Factors related to physical functioning decline after cardiac surgery in older patients: A multicenter retrospective study. Issue 3 (September 2019) - Itagaki, Atsunori; Saitoh, Masakazu; Okamura, Daisuke; Kawamura, Tomonori; Otsuka, Shota; Tahara, Masayuki; Mori, Yuji; Kamisaka, Kenta; Ochi, Yusuke; Yuguchi, Satoshi; Kato, Michitaka; Morisawa, Tomoyuki; et al.
Highlights: Physical functioning declined in 17% of older patients after cardiac surgery. The decline could be predicted by several factors, including some that are modifiable. Additional rehabilitation interventions to routine practice might reduce the decline. Abstract: Background: As few studies have examined physical functioning changes after cardiac surgery, the factors related to the decline in physical functioning remain unclear. This study aimed to investigate the factors related to physical functioning decline after cardiac surgery in older patients. Methods: The final study sample consisted of 523 older (≥65 years) patients (age 74.2 ± 6.1 years, 66% male) who underwent cardiac surgery at 8 Japanese institutions. We excluded patients who were unable to walk independently or had a slow gait speed (<0.8 m/s) before surgery, and those who were unable to regain independent walking after surgery. We divided the patients into two groups, a decline-in-gait-speed group and a non-decline-in-gait-speed group, according to whether their gait speed was less than 0.8 m/s at discharge. We analyzed patients' clinical characteristics to identify the factors that predicted the postoperative decline in gait speed. Results: Eighty-nine patients (17.0%) showed a postoperative decline in gait speed. Multivariate logistic regression analysis showed that the following factors predicted a postoperative decline in gait speed: age [odds ratio (OR) 1.06, 95% confidence interval (CI) 1.02–1.11]; estimated glomerular filtration rate (OR 0.98, CI 0.96–0.99); preoperative gait speed (OR 0.01, CI 0.00–0.08); and the postoperative day on which the patient could walk independently (OR 1.08, CI 1.02–1.14). Conclusions: Physical functioning declined in 17% of patients after surgery. The decline could be predicted by several clinical factors, including some that are modifiable. These results suggest that further interventional research on rehabilitation before and after cardiac surgery for older patients might help overcome the decline in physical functioning.